2008
DOI: 10.1038/onc.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role of DDX3 in breast cancer biogenesis

Abstract: Benzo [a]pyrene diol epoxide (BPDE), the active metabolite of benzo [a]pyrene present in tobacco smoke, is a major cancer-causing compound. To evaluate the effects of BPDE on human breast epithelial cells, we exposed an immortalized human breast cell line, MCF 10A, to BPDE and characterized the gene expression pattern. Of the differential genes expressed, we found consistent activation of DDX3, a member of the DEAD box RNA helicase family. Overexpression of DDX3 in MCF 10A cells induced an epithelial-mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
227
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(249 citation statements)
references
References 38 publications
18
227
4
Order By: Relevance
“…For example, upon HIV infection and in a number of cancers, including acute myeloid leukemia and breast cancer, DDX3 expression is greatly upregulated. [37][38][39] Consequently, it would be of interest to investigate whether elevated levels of DDX3 might have any effect on cellular translation activities during HIV infection and during cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, upon HIV infection and in a number of cancers, including acute myeloid leukemia and breast cancer, DDX3 expression is greatly upregulated. [37][38][39] Consequently, it would be of interest to investigate whether elevated levels of DDX3 might have any effect on cellular translation activities during HIV infection and during cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, DDX3, like Ded1p, has been implicated in cell growth control, although whether it plays a positive or negative role remains unclear. 22,30,37,46 At least in some cases, increased expression of DDX3 was found to promote cell growth, proliferation and even transformation. 22,30,37,46 Because a number of cellular proteins involved in regulating cell growth and programmed cell death are produced via IRES-mediated translation under stressed conditions, 47 it would be of interest to examine whether and how DDX3 participates in such cellular IRES-mediated translation.…”
Section: Nuclear Export Of Metazoan Ded1p/ddx3 Homologsmentioning
confidence: 99%
“…Many characterized RNA helicases have been found to be fundamental in essential cellular processes (1,26). In recent years, a few RNA helicases have been found to participate in cancer development even though their detailed molecular mechanisms remain largely undiscovered (27)(28)(29)(30)(31)(32)(33). Furthermore, despite the characterization of several DEAD/DEAH proteins, few specific inhibitors targeting these ATP-dependent helicases have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated expression of DDX3 was found in a highly aggressive metastatic breast cancer cell line, MDA-MB-231, as compared with non-metastatic MCF-7 cells, which show its potential role in aggressive breast cancers and associated metastasis. 5,6 We have previously reported that overexpression of DDX3 in immortalized non-turmorigenic MCF10A cells promoted neoplastic transformation as indicated by down regulation of a cell adhesion molecule, E-cadherin. 5 Down-regulation of E-cadherin is a common feature of a variety of metastatic epithelial tumors, including those of the lung, breast and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elevated expression of DDX3 was found in a highly aggressive metastatic breast cancer cell line, MDA-MB-231, as compared with non-metastatic MCF-7 cells, which show its potential role in aggressive breast cancers and associated metastasis. 5,6 We have previously reported that overexpression of DDX3 in immortalized non-turmorigenic MCF10A cells promoted neoplastic transformation as indicated by down regulation of a cell adhesion molecule, E-cadherin.5 Down-regulation of E-cadherin is a common feature of a variety of metastatic epithelial tumors, including those of the lung, breast and prostate cancer.5,7-9 Hypoxic regions of solid tumors were considered to be the primary sites for the generation of the metastatic phenotype and have been demonstrated to be chemo and radio-resistant. [10][11][12][13][14] We have also reported that hypoxia inducible factor (HIF-1) induce the expression of DDX3 in two different breast cell lines by binding directly or indirectly to the hypoxia-response element (HRE) in the DDX3 proximal promoter.…”
mentioning
confidence: 99%